Integrasi Literasi Digital dalam Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Della Fusvita; Ananda Talia Salsa Billa; Wiwinda .; Randi .; Hendro Ade Saputra (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
The problem in this study is that the integration of digital literacy in the learning process at elementary schools has not been implemented optimally. Low teacher competence in utilizing technology, limited facilities and infrastructure, unequal internet access, and the low level of students’ digital literacy culture are the main factors hindering the implementation of digital-based learning.  This study aims to analyze the integration of digital literacy in improving the quality of learning in elementary schools and to identify the supporting and inhibiting factors in its implementation. This study employed a qualitative approach using a library research method. Data were collected through documentation techniques from various national and international journals, scientific articles, and other relevant sources published within the last five years. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the integration of digital literacy has a significant influence on improving the quality of learning, particularly in enhancing students’ understanding, learning motivation, active participation, critical thinking skills, and problem-solving abilities. The use of interactive digital media such as learning videos, educational applications, and online learning platforms is able to create more innovative, engaging, and effective learning experiences. However, the successful implementation of digital literacy is strongly influenced by teacher competence, the availability of supporting facilities, internet access, and school policy support. Therefore, integrated and sustainable efforts are needed to develop digital literacy in order to support the improvement of education quality in the digital era.